Where is it going - Scott, Lee; National Geographic Society (U.S.). (Washington, D.C. National Geographic Society, 2002)
"Think and discuss. Where is it going?"
At head of title: National Geographic.
"National Geographic windows on literacy." -- Cover.
Keywords: Readers (Primary).; Motor vehicles -- Juvenile literature; Transportation -- Juvenile literature; Trucks -- Pictorial works; Motor vehicles -- Pictorial works